Identifying and Evaluating Critical Success Factors for Industrialized Building Systems Implementation: Malaysia Study - Khaled M., Amtered El-Abidi; George, Ofori; Sharifah Akmam, Syed Zakaria; Mohammad Abdul, Mannan; Noor Faisal, Abas (Springer, 2019)
The drive toward implementing an industrialized building system (IBS) in Malaysia is in line with Malaysia’s Construction Industry Transformation Plan 2016–2020, which seeks to increase more than double the construction industry’s productivity. IBS is able to accelerate the construction timeline, provide a safer working environment on site, produce a higher quality of construction, and save costs. Although the introduction of IBS in Malaysia is not new, its acceptance has not been extensive, and IBS implementation is still slow. Thus, to support the successful implementation of IBS, it is vital to determine the factors that influence the achievement of this aspiration. Therefore, this study aims to identify and evaluate the critical success factors (CSFs) that contribute to the smooth implementation of the IBS dimensions within the context of the Malaysian construction industry. By doing so, the uptake of IBS can be accelerated. In order to consolidate the set of candidate success factors, these CSFs were identified from the literature review and confirmed through a self-administered survey questionnaire. Then, the value of importance of each CSF was calculated in a second survey. Based on the factor analysis, 15 CSFs were identified and grouped into five major elements: strategy, sources of funding, process, people, and enabler, with each factor comprising its own set of components. The findings indicate that the CSFs in IBS implementation have different priorities and weights.